Ion sieve with high temperature resistance and high temperature stability, its preparation method and use
The ion sieve with a specific composition addresses the instability of conventional impurity removal materials by maintaining high temperature stability and continuous adsorption, improving glass production efficiency and quality.
Patent Information
- Application Number
- JP2023578803
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-12-23
- Filing Date
- 2023-06-07
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-06-07
AI Technical Summary
Conventional impurity removal materials for glass chemical reinforcement suffer from high temperature instability, leading to frequent bath replacements, reduced production efficiency, and increased costs due to impurity contamination and phase transitions, which affect the quality and mechanical strength of the glass.
Development of an ion sieve with a specific composition (SiO2 46-60 mol%, Al2O3 3-16 mol%, Y2O3 0-3 mol%, R2O 33-45 mol%) that exhibits high temperature resistance and stability, allowing continuous adsorption of impurities like lithium ions in a 480°C salt bath for 24 hours without significant phase transitions.
The ion sieve maintains stability in high-temperature environments, preventing impurity release and surface defects in glass products, enhancing production efficiency and reducing costs by minimizing bath replacements.
Smart Images

Figure 2025501821000001_ABST
Abstract
Description
[Technical field]
[0001] (CROSS REFERENCE TO RELATED APPLICATIONS) This application claims priority based on a Chinese application filed with the State Intellectual Property Office of China on December 23, 2022, bearing application number 202211665025.4 and entitled "Ion sieve with high temperature resistance and high temperature stability, its preparation method and use", the entire contents of which are incorporated herein by reference.
[0002] The present application relates to the technical field of ion sieves, in particular to the technical field of impurity removal from salt baths for chemically strengthening glass, and specifically to an ion sieve with high temperature resistance and stability, its preparation method and use. [Background technology]
[0003] In the chemical strengthening process of glass, alkali metal ions with small ionic radius (e.g. Na + , Li + ) in the salt bath is the alkali metal ion with a large ionic radius (e.g., K + , Na + ), causing a "clogging phenomenon" within a certain depth range, forming a specific stress distribution, preventing the extension of microcracks in the glass, and thus achieving the purpose of increasing the strength of the glass. Furthermore, alkali metal ions with small ionic radii increasingly enter the salt bath from the glass, leading to an increase in the amount of alkali metal ions with small ionic radii in the salt bath, and the increased amount of alkali metal ions with small ionic radii become impurity ions in the salt bath. The alkali metal ions with small ionic radii in the salt bath (such as Li + When the amount of Li in the salt bath is too high, the normal progress of chemical strengthening is seriously hindered, the stress level of the strengthened glass is reduced, and the mechanical strength is greatly reduced, so that the performance of the final product cannot meet the requirements for use. +If the amount of is increased, the degree of lithium-sodium exchange when the lithium aluminosilicate glass is chemically strengthened will be significantly reduced, and the dimensional increment of the glass after strengthening will decrease rapidly, making it impossible to meet the requirements for the dimensional deviation range of the glass in the application of mobile phone covers, resulting in an increase in the dimensional defect rate of the chemically strengthened glass.
[0004] In view of the above, the industry has proposed the introduction of impurity ion removing materials into the salt bath. Here, the impurity ion removing material is a material that can remove excess small ionic radius alkali metal ions (e.g., Li + ) and remove the small ionic radius alkali metal ions (e.g. Li + ) within a specified range, thereby ensuring the normal use of the salt bath and preventing the amount of alkali metal ions with small ionic radius (e.g. Li + ) is too high, which can prevent degradation of the performance and quality of the glass.
[0005] The materials commonly used in glass factories to remove impurity ions include phosphates and ion sieves. The principle of removing impurity ions with phosphates is to form a precipitate by the reaction between phosphate ions and impurity ions. For example, when powdered sodium phosphate is added to a salt bath, lithium phosphate precipitates are formed by the reaction between phosphate ions and lithium ions, and thus the impurity Li + However, the lithium phosphate makes the salt bath turbid, so it must be used after a long time to clear up, and some lithium phosphate granules are likely to adhere to the surface of tempered glass, causing defects in the glass. That is, when phosphate is used as an impurity ion removing material, the effect of improving the salt bath is limited, and in order to ensure the performance and quality of tempered glass, the salt bath must be frequently replaced within a short period of time, which is disadvantageous to improving the efficiency of mass production and also leads to an increase in the tempering cost. And if too much lithium phosphate precipitates at the bottom of the salt bath, the effective functional area of the salt bath is reduced, making it difficult to clean the tempering bath.
[0006] In glass factories, in order to ensure mass production efficiency, it is more desirable to continuously put glass to be tempered into the salt bath to obtain chemically tempered glass that meets the requirements through tempering, and it is also more desirable to increase the temperature of the salt bath to shorten the glass tempering time. To achieve this goal, a measure is needed to effectively control the amount of impurity ions in the salt bath. If the impurity ion removing material cannot be used for a long time and needs to be replaced frequently, the tempering process will be interrupted, the mass production efficiency will be impaired, and the amount of impurity ion removing material will increase. In the process of extracting the impurity ion removing material, a large amount of molten salt will also be extracted. These two reasons lead to an increase in the tempering cost. Therefore, in order to reduce the amount of molten salt used, improve production efficiency, and reduce production costs, an impurity ion removing material that can be used stably for a long time in a high-temperature salt bath is needed.
[0007] After finding out the shortcomings of using phosphate as an impurity ion removal material, the applicant of the present application developed an ion sieve material capable of adsorbing impurity ions in a salt bath. The applicant's prior patent application CN112645610A discloses a highly stable ion sieve free of boron and phosphorus and its use, which solves the problem of insufficient adsorption capacity for lithium ions in a high-temperature salt bath and poor adsorption rate, especially poor adsorption rate for poisoned lithium ions, in the production process of chemically strengthened glass covers. After adding the ion sieve developed by the applicant, the content of impurity ions in the salt bath can be well suppressed, and a series of problems when using phosphate can be avoided, but further improvement of high temperature resistance and high temperature stability is desired. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Chinese Patent Application No. 112645610A Summary of the Invention [Problem to be solved by the invention]
[0009] The present application aims to provide an ion sieve with high temperature resistance and high temperature stability, which can overcome the drawbacks of the prior art that impurity ion removal materials need to be further improved in high temperature resistance and high temperature stability, and its preparation method and use. The ion sieve has excellent high temperature resistance, can be stably used in a high temperature salt bath for a long time, and has excellent high temperature stability, for example, can continuously adsorb impurity lithium ions for 24 hours in a salt bath at 480°C, eliminating the need to frequently replace the salt bath, can improve the production efficiency of chemically strengthened glass, and can reduce the production cost of chemically strengthened glass, and can be widely used.
[0010] The inventors of the present application have conducted intensive research and have ascertained the reason why it is difficult to further improve the high temperature resistance and high temperature stability of conventional impurity ion removal materials. That is, when a general silicon-based ion sieve is used in a high-temperature salt bath for a long time, a significant crystal phase transition occurs, and the ion sieve material in which the crystal phase transition occurs loses its lithium ion adsorption effect, and may even release lithium ions into the salt bath. And the ion sieve material in which the crystal phase transition occurs has significant defects such as releasing a large amount of impurity substances that contaminate the salt bath into the salt bath, impairing the quality of the glass after strengthening, and causing granules to adhere to the surface of the finished glass product after strengthening. In view of this, the inventors have conducted further research and completed the present invention. The present invention solves the problem that the crystal phase transition of the silicon-based ion sieve in the chemical strengthening treatment process causes the lithium ions to be unable to be stably adsorbed for a long time, releasing a large amount of impurity substances, and impairing the life and high temperature stability of the salt bath. [Means for solving the problem]
[0011] To achieve the above object, in a first aspect, the present application provides an ion sieve having high temperature resistance and stability. In the present application, the composition of the ion sieve includes, in terms of the mole percentage of each oxide in the ion sieve, 46-60 mol % of SiO, 3-16 mol % of AlO, 0-3 mol % of YO, and 33-45 mol % of RO, where RO is an alkali metal oxide, and the ion sieve is [ka] is greater than or equal to 1, [ka] However, in the ion-sieving Raman spectrum, -1 Q after Gaussian deconvolution fitting to the bands in the range 3 is the corresponding area of Q 3 However, in silicon-oxygen tetrahedra with only one non-bridging oxygen, - Stretching vibration peak, [ka] However, in the ion-sieving Raman spectrum, -1 Q after Gaussian deconvolution fitting to the bands in the range 2 is the corresponding area of Q 2 However, in silicon-oxygen tetrahedra with only two non-bridging oxygens, Si-O - This is a stretching vibration peak.
[0012] In some alternative embodiments, the ion sieve has a crystalline content of less than 10 wt. % after placing the ion sieve in a salt bath at 480° C. for 24 hours.
[0013] In some alternative embodiments, [ka] teeth [ka] Meet the following.
[0014] In some alternative embodiments, the composition of the ion sieve satisfies 52.0 > 0.85 x SiO2 + 0.15 x Al2O3 + 1.65 x Y2O3 > 45.3 in terms of mole percentage of each oxide in the ion sieve. Preferably, the composition of the ion sieve further satisfies 20.0≧0.50×R2O≧16.0, in terms of the mole percentage of each oxide in the ion sieve, where R2O is Na2O and / or K2O, and more preferably R2O is Na2O.
[0015] In some alternative embodiments, the ion sieve has a molar percentage of SiO2 between 49 and 60 mol%, and / or a molar percentage of Al2O3 between 3 and 15 mol%, and / or a molar percentage of Y2O3 between 1 and 3 mol%, and / or a molar percentage of R2O between 33 and 40 mol%.
[0016] In some alternative embodiments, the composition of the ion sieve further includes, in terms of the molar percentages of each oxide in the ion sieve, 0-3 mol% ZnO, 0-3 mol% CaO, 0-3 mol% MgO, 0-3 mol% P2O5, and 0-3 mol% B2O3, and the sum of the molar percentages of ZnO+CaO+MgO+P2O5+B2O3 is 5 mol% or less.
[0017] Preferably, the ion sieve contains little P2O5 and / or B2O3. Preferably, the ion sieve contains little Li2O.
[0018] In some alternative embodiments, when the ion sieve with a mass percentage of 1% by weight based on the mass of the salt bath is put into a 480 °C salt bath containing 105 ± 10 ppm of impurity lithium ions, the change curve of the change in the lithium ion concentration y in the salt bath over time x satisfies the function of y = A1×exp(-x / b1)+A2×exp(-x / b2)+C0, where exp is an exponential function, 100 > A1 > 30, 0 < A2 < 31, 0 < b1 < 5, 0 < b2 < 25, and 0 < C0 < 50, and the unit of x is time.
[0019] In some alternative embodiments, the ion sieve is granular, sheet-like or porous, preferably granular, and preferably the particle size of the granular ion sieve is 1 - 10 mm.
[0020] On a second aspect, the present application provides a method for preparing an ion sieve according to the first aspect. This preparation method includes steps of weighing each raw material according to a formulation instruction and uniformly mixing them, then melting at a temperature of 1300 - 1650 °C to obtain a liquid material, and preparing it as a granular, sheet-like or porous material.
[0021] In some alternative embodiments, granular ion sieves are formed by water quenching, and the temperature of water quenching is 10 - 80 °C.
[0022] In some alternative embodiments, sheet-like ion sieves are formed by rolling or drawing with an external force.
[0023] In some alternative embodiments, porous ion sieves are formed by introducing a foaming agent.
[0024] On a third aspect, the present application provides a method for removing impurities from a salt bath for chemical strengthening of glass. This impurity removal method includes a step of introducing the ion sieve according to the first aspect into an impurity-removing waiting salt bath at 350 - 550 °C to perform an adsorption reaction of impurity ions.
[0025] In some alternative embodiments, the amount of the ion sieve used is 0.5 to 5.0% by weight of the salt bath for removing impurities.
[0026] In some alternative embodiments, the adsorption reaction time is 0.1 to 48.0 hours.
[0027] In some optional embodiments, the content of impurity ions in the impurity removal salt bath is 1 to 1000 ppm.
[0028] In a fourth aspect, the present application provides a method for preparing chemically strengthened glass, the method comprising the steps of: introducing a glass to be strengthened and an ion sieve according to the first aspect into a salt bath for chemically strengthening glass that is free of impurity ions, and chemically strengthening the glass to be strengthened to prepare the chemically strengthened glass.
[0029] This preparation method is a method for realizing online impurity removal of ion sieves, which realizes that the impurity removal process of ion sieves is carried out simultaneously with the tempering process of glass, so there is no need to pause the tempering process and there is no need to frequently replace the salt bath, which can improve the production efficiency of chemically tempered glass and reduce the production cost of chemically tempered glass.
[0030] (Beneficial Effects) Through detailed research into ion sieves, it has been found that an ion sieve with a specific composition and meeting specific structural requirements has excellent high temperature resistance and high temperature stability, and even if the ion sieve is placed in a high temperature salt bath for a relatively long time, it hardly undergoes significant crystal phase transition, has a stable structure, does not release a large amount of impurity substances that contaminate the salt bath, and does not produce significant defects such as granularity on the surface of the finished glass product after tempering. The ion sieve of the present application can continuously and stably adsorb impurity ions in a salt bath at 480°C for 24 hours, for example, can stably adsorb lithium ions that have an adverse effect on glass tempering, and can ensure that the surface quality of the finished glass product after tempering meets the requirements. If the structure of the ion sieve does not meet the specific structural requirements of the present application, after being placed in a high-temperature salt bath for a relatively long time, a significant crystal phase transition will occur, and the adsorption ability and adsorption effect of the ion sieve for impurity ions will be significantly reduced. As a result, after being placed in a high-temperature salt bath for a relatively long time, impurity ions and other impurity substances will be released back from the ion sieve into the salt bath, contaminating the salt bath, and significant defects such as granular defects will occur on the surface of the finished glass product after tempering. [Brief description of the drawings]
[0031] In order to more clearly explain the technical ideas of the embodiments of the present invention, the drawings used in the embodiments are briefly described below. The drawings described are only for illustrating some embodiments of the present invention, and are not intended to limit the scope. Those skilled in the art can obtain other related drawings based on these drawings without using inventive abilities. [Figure 1a] 1 shows initial XRD patterns of ion sieves according to Examples 1 to 4. [Figure 1b] 2 shows initial XRD patterns of ion sieves according to Comparative Examples 1 to 4. [Figure 2a] 1 shows XRD patterns of ion sieves according to Examples 1 to 4 after adsorbing lithium ions in a test salt bath at 480° C. for 24 hours. [Figure 2b]1 shows XRD patterns of ion sieves according to Comparative Examples 1 to 4 after adsorbing lithium ions in a test salt bath at 480° C. for 24 hours. [Figure 3a] 1 is a graph showing the tendency of lithium ion concentration to change over time when the ion sieves according to Examples 1 to 4 were used in a test salt bath at 480° C. [Figure 3b] 1 is a graph showing the tendency of change over time in lithium ion concentration when the ion sieves according to Comparative Examples 1 to 4 were used in a test salt bath at 480° C. [Figure 4] 1 is a graph showing fitting results of the tendency of change in lithium ion concentration over time according to Example 1. [Diagram 5] 13 is a graph showing fitting results of the tendency of change in lithium ion concentration over time according to Example 2. [Figure 6] 13 is a graph showing fitting results of the tendency of lithium ion concentration to change over time according to Example 3. [Figure 7] 13 is a graph showing fitting results of the tendency of lithium ion concentration to change over time according to Example 4. [Figure 8] 1 is a diagram showing the surface of a tempered glass product obtained by directly using the ion sieve according to Example 1 in a chemical tempering process. [Figure 9] 1 is a diagram showing the surface of a tempered glass product obtained by directly using the ion sieve according to Comparative Example 1 in a chemical tempering process. [Figure 10] 1 is a diagram showing the surface of a tempered glass product obtained by directly using the ion sieve according to Comparative Example 2 in a chemical tempering process. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0032] The range endpoints and any values disclosed herein are not limited to the specific ranges or values, and these ranges or values should be understood to include values close to these ranges or values. In the case of numerical ranges, the combination of each range endpoint with each range endpoint and each specific value, and each specific value can be combined to obtain one or more new numerical ranges, which should also be considered specifically disclosed herein. The terms "optionally" and "optionally" mean that they may or may not be inclusive (they may or may not be present).
[0033] The measurement method according to the present application is as follows. 1. Raman Spectroscopic Measurement of Ion Sieves The ion sieve is pulverized to a particle size of less than 75 μm and measured using a laser Raman spectrometer to obtain a Raman spectrum. Measurement conditions: Wave number range 100-1500 cm -1 and the spectral resolution is 1-2 cm -1 It is. The laser Raman spectrometer used in this application is manufactured by Renishaw Ltd., UK, and has the model number INVIA.
[0034] 2. XRD pattern measurement of ion sieves (1) XRD pattern measurement of initial ion sieve The initial ion sieve not used for removing salt bath impurities is pulverized to a particle size of less than 75 μm and measured using an X-ray diffractometer to obtain an XRD diffraction peak profile, i.e., an XRD pattern. Measurement conditions: incident angle range 2θ = 10° to 80°, scan speed 6° / min, operating voltage 40 kV, and operating current 30 mA. (2) XRD pattern measurement of ion sieve after use in removing salt bath impurities The initial ion sieve is placed in a test salt bath at 480°C containing 1000 ppm or less of impurity lithium ion, and removed after 24 hours of impurity removal. The removed ion sieve is pulverized to a particle size of less than 75 μm, and measured using an X-ray diffractometer to obtain an XRD diffraction peak profile, i.e., an XRD pattern. The test salt bath used in this application is a sodium nitrate salt bath containing 105±10 ppm of impurity lithium ion. Measurement conditions: incident angle range 2θ = 10° to 80°, scan speed 6° / min, operating voltage 40 kV, and operating current 30 mA. The X-ray diffraction apparatus used in this application is a Shimadzu XRD_6100.
[0035] 3. Measurement of the crystal content in ion sieves The content of crystals in the ion sieve is expressed as the ratio of the crystal peak area in the XRD pattern of the ion sieve after it has been used to remove impurities from the salt bath, i.e., the ratio of the crystal peak area fitted based on the XRD pattern to the total fitted peak area is the crystal content. In this application, an X-ray diffractometer is used to measure the ion sieve after it has been used to remove impurities from the salt bath, and the measurement result file (RAW format) from the X-ray diffractometer is imported into X-ray diffraction data Rietveld refinement software (e.g., Jade, Gsas, Fullprof, Maud) for fitting and calculation. In this application, the measurement result file (RAW format) from the X-ray diffractometer is imported into Jade for fitting and calculation to obtain the content of crystals in the ion sieve.
[0036] 4. Measuring the concentration (also called content) of lithium ions in the salt bath The ion sieve is placed in a salt bath to remove impurities, and the concentration of lithium ions in the salt bath at different times is measured using an atomic absorption spectrophotometer with time as a variable.
[0037] In a first aspect, the present application provides an ion sieve having high temperature resistance and high temperature stability. The composition of the ion sieve includes, in terms of the mole percentage of each oxide in the ion sieve, 46-60 mole % of SiO2, 3-16 mole % of Al2O3, 0-3 mole % of Y2O3, and 33-45 mole % of R2O. R2O is an alkali metal oxide. The ion sieve comprises: [ka] is greater than or equal to 1, [ka] However, in the ion-sieving Raman spectrum, -1 Q after Gaussian deconvolution fitting to the bands in the range 3 is the corresponding area of Q 3 However, in silicon-oxygen tetrahedra with only one non-bridging oxygen, - Stretching vibration peak, [ka] However, in the ion-sieving Raman spectrum, -1 Q after Gaussian deconvolution fitting to the bands in the range 2 is the corresponding area of Q 2 However, in silicon-oxygen tetrahedra with only two non-bridging oxygens, Si-O - This is a stretching vibration peak. area [ka] and area [ka] The units are the same.
[0038] The principle of action of the oxides of each component is as follows: SiO2 is for forming covalent bonds and constituting the skeleton of the ion sieve network structure, and the selection of its structure and content directly affects the adsorption of the ion sieve network structure and the thermal stability of the ion sieve in a high temperature environment. If the SiO2 content is too low, the moldability of the ion sieve is poor, and if the SiO2 content is too high, the viscosity of the composition becomes relatively high, making it difficult to melt. Therefore, in the present application invention, the molar percentage of SiO2 is 46 to 60 mol%. In some embodiments, the content of SiO2 is 46 mol%, 47 mol%, 48 mol%, 49 mol%, 50 mol%, 51 mol%, 52 mol%, 53 mol%, 54 mol%, 55 mol%, 56 mol%, 57 mol%, 58 mol%, 59 mol%, 60 mol%, etc., as well as ranges and subranges defined by any of the above values. In embodiments, any of the above ranges can be combined with any other range.
[0039] Al2O3 is a component of the network structure, and is advantageous in improving the adsorption rate of impurity ions during the adsorption process of the ion sieve, and in improving the decomposition resistance of the ion sieve in a high-temperature environment. However, if the amount of aluminum oxide is too much, it becomes difficult to form the ion sieve. Therefore, in the present invention, the molar percentage of Al2O3 is 3 to 16 mol%. In some embodiments, the content of Al2O3 is 3 mol%, 4 mol%, 5 mol%, 6 mol%, 7 mol%, 8 mol%, 9 mol%, 10 mol%, 11 mol%, 12 mol%, 13 mol%, 14 mol%, 15 mol%, 16 mol%, etc., as well as ranges and subranges defined by any of the above values. In embodiments, any of the above ranges can be combined with any other range.
[0040] A suitable amount of Y2O3 can improve the hardness and chemical stability of the ion sieve, but a relatively high content of Y2O3 increases the tendency of the ion sieve to devitrify. Therefore, in the present invention, the molar percentage of Y2O3 is 0-3 mol%. In some embodiments, the content of Y2O3 is 0, 0.5 mol%, 1 mol%, 1.5 mol%, 2 mol%, 2.5 mol%, 3 mol%, etc., as well as ranges and subranges defined by any of the above values. In embodiments, any of the above ranges can be combined with any other range.
[0041] On the one hand, the alkali metal oxide R2O can provide alkali metal ions for ion exchange, which contributes to ensuring the adsorption capacity of the ion sieve for impurity ions, and on the other hand, it provides free oxygen and affects the structural stability of the ion sieve. That is, the content of R2O directly affects the ability of the ion sieve to adsorb impurity ions and the stability of the ion sieve in a high-temperature salt bath. Therefore, in the present application, the molar percentage of R2O is 33-45 mol%. In some embodiments, the content of R2O is 33 mol%, 34 mol%, 35 mol%, 36 mol%, 37 mol%, 38 mol%, 39 mol%, 40 mol%, 41 mol%, 42 mol%, 43 mol%, 44 mol%, 45 mol%, etc., as well as ranges and subranges defined by any of the above values. In embodiments, any of the above ranges can be combined with any other range.
[0042] In some alternative embodiments, the ion sieve has a crystalline content of less than 10% by weight after the ion sieve is placed in a salt bath at 480° C. for 24 hours, the crystalline content being expressed as a percentage of the crystalline peak area in the XRD pattern of the ion sieve.
[0043] In the present invention, the Gaussian deconvolution fitting is performed by importing a measurement result file (.txt format) from a laser Raman spectrometer into Origin (for example, Origin2022 version) and performing a Gaussian deconvolution fitting at 830 to 1230 cm -1By selecting a band within the range and performing deconvolution fitting and calculation using a Gaussian function, Q 3 and Q 2 The corresponding areas of each of the fitted Q 3 Area and fitted Q 2 The ratio of the area [ka] It is.
[0044] In some alternative embodiments, [ka] but [ka] Meet the following.
[0045] In some embodiments, [ka] The value of is 1.00, 1.05, 1.30, 1.50, 2.00, 2.30, 2.50, 2.80, 3.00, etc., as well as ranges and subranges defined by any of the above values. In embodiments, any of the above ranges can be combined with any other range. According to the inventor's research and verification, the ion sieve of the present invention having a specific composition and satisfying specific structural requirements has excellent high temperature resistance and high temperature stability, and even if the ion sieve is placed in a high temperature salt bath for a relatively long time, there is almost no significant crystal phase transition and the structure is stable.
[0046] In some alternative embodiments, the composition of the ion sieve satisfies the following condition: 52.0 > 0.85 x SiO2 + 0.15 x Al2O3 + 1.65 x Y2O3 > 45.3, where the mole percentage of each oxide in the ion sieve is 52.0 > 0.85 x SiO2 + 0.15 x Al2O3 + 1.65 x Y2O3 > 45.3. When using this alternative embodiment, detailed research by the inventors of the present application has revealed that the degree of influence of each major component oxide on high temperature stability is different, and when the above condition is met, [ka] It is possible to obtain an ion sieve having a specific structure that satisfies the condition of 1 or more, and this not only significantly improves the structural stability of the ion sieve, but is also advantageous for melting and forming the ion sieve.
[0047] In some embodiments, the value of 0.85×SiO2+0.15×Al2O3+1.65×Y2O3 is 45.3, 46.0, 47.0, 48.0, 49.0, 50.0, 51.0, 51.5, 52.0, etc., as well as ranges and subranges defined by any of the above values. In embodiments, any of the above ranges can be combined with any other range.
[0048] In the above optional schemes, Y2O3 may or may not be contained. When Y2O3 is contained, the effect of Y2O3 on the structural stability of the ion sieve is much greater than that of SiO2 and Al2O3, so controlling the content of Y2O3 within the above conditions is more favorable for improving high temperature stability.
[0049] In the present invention, the ion sieve may further contain other components as long as it satisfies 52.0≧0.85×SiO2+0.15×Al2O3+1.65×Y2O3≧45.3.
[0050] In some selectable embodiments, the composition of the ion sieve satisfies 20.0 ≧ 0.50 × R2O ≧ 16.0 in terms of the molar percentage of each oxide in the ion sieve, where R2O is Na2O and / or K2O. On the one hand, the alkali metal oxide can provide alkali metal ions used in ion exchange, contributing to ensure the adsorption capacity of the ion sieve for impurity ions, and on the other hand, can provide free oxygen and affect the structural stability of the ion sieve. In the present invention, if 0.50 × R2O is within a range of 16.0 to 20.0, the ion sieve has excellent adsorption capacity and ensures structural stability. When chemical strengthening is performed on general glass, exchange occurs mainly between Na ions and Li ions contained in the glass and K ions and Na ions in the salt bath. The impurity ions present in the salt bath are mainly Li ions released from the glass to the salt bath. If the R2O in the ion sieve is Na2O and / or K2O, it can better adsorb impurity ions in the salt bath and remove impurities from the salt bath.
[0051] Preferably, R2O is Na2O. When chemically strengthening glass, Na-Li exchange can obtain a deeper compressive stress layer, which is more advantageous in improving the impact resistance of glass. To achieve this, Li ions in the glass are replaced by Na ions in the salt bath, which enter the salt bath and become impurity ions. According to the inventor's research, if the concentration of impurity lithium ions in the salt bath is too high, it is very disadvantageous to strengthening the glass. If all of the R2O in the ion sieve is Na2O, it can better achieve adsorption to impurity ions in the salt bath and removal of impurities from the salt bath.
[0052] Preferably, in the ion sieve, the molar percentage of SiO2 is 49-60 mol %. Preferably, in the ion sieve, the molar percentage of Al2O3 is 3-15 mol %. Preferably, in the ion sieve, the molar percentage of Y2O3 is 1-3 mol %. Preferably, in the ion sieve, the molar percentage of R2O is 33 to 40 mol %.
[0053] The ion sieve according to the present invention may further contain other metal oxides. Preferably, the composition of the ion sieve further contains, in terms of the molar percentage of each oxide in the ion sieve, 0-3 mol% ZnO, 0-3 mol% CaO, 0-3 mol% MgO, 0-3 mol% P2O5, and 0-3 mol% B2O3. Preferably, the total molar percentage of ZnO+CaO+MgO+P2O5+B2O3 is 5 mol% or less. This optional embodiment is more advantageous for the high temperature stability of the ion sieve, can reduce the amount of crystal precipitation, and is more advantageous for preventing the adsorption efficiency of the ion sieve from decreasing.
[0054] In the present invention, P2O5 and B2O3 may be included in the components of the ion sieve, but if the content of these components is too high, the chemical durability of the ion sieve is impaired and it is prone to random erosion of the surface of glass and microcrystalline glass when used in a high-temperature salt bath. Therefore, the ion sieve of the present invention preferably contains almost no P2O5 and / or B2O3. Here, "almost no" means that at least one of P2O5 and B2O3 is not added to the ion sieve or is not introduced as a raw material, but may be present in a very small amount as a contaminant or impurity.
[0055] In the present invention, the ion sieve contains almost no Li2O. If the ion sieve contains Li2O, it is likely to impair the effect of the ion sieve in adsorbing impurity lithium ions.
[0056] In some selectable embodiments, based on the mass of the salt bath, when the ion sieve with a mass percentage of 1 wt% is placed in a 480°C salt bath containing 105±10 ppm of impurity lithium ions, the change curve of the lithium ion concentration y in the salt bath over time x satisfies the function of y = A1×exp(-x / b1)+A2×exp(-x / b2)+C0, where exp is the exponential function, 100 > A1 > 30, 0 < A2 < 31, 0 < b1 < 5, 0 < b2 < 25, 0 < C0 < 50, and the unit of x is h (hour). According to this selectable embodiment, the ion sieve according to the present application can achieve continuous and stable adsorption of impurity lithium ions in a high-temperature salt bath for a long time. That is, the ion sieve according to the present application has excellent high-temperature stability and impurity ion adsorption ability.
[0057] In the above function, if a data relationship (mathematical model) is established based on the predetermined discrete data of y and x, a series of tiny straight-line segments are obtained and these interpolation points are connected to form a curve, a smooth curve is formed. This curve is represented by exp (exponential function), and A1, A2, b1, b2, and C0 are all coefficients and are determined by the predetermined discrete data.
[0058] Those skilled in the art can select the shape and particle size of the ion sieve according to actual needs.
[0059] In some alternative embodiments, the ion sieve is granular, sheet-like or porous, preferably granular, and preferably the granular ion sieve has a particle size of 1-10 mm. In some embodiments, the granular ion sieve has a particle size of 1 mm, 1.5 mm, 2 mm, 2.5 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, etc., as well as ranges and subranges defined by any of the above values. Preferably, the granular ion sieve has a particle size of 2-5 mm. In embodiments, any of the above ranges can be combined with any other range. Herein, "particle size of ion sieve" refers to the maximum diameter of the ion sieve granules.
[0060] In a second aspect, the present application provides a method for preparing the ion sieve according to the first aspect, comprising the steps of weighing and uniformly mixing each raw material according to a formula (components of the ion sieve according to the first aspect), melting the mixture at a temperature of 1300-1650°C to obtain a liquid material, and preparing the liquid material as granules, sheets or porous materials.
[0061] In some alternative embodiments, the melting time is 1 hour or more, which can ensure that each raw material is completely melted and mixed uniformly.
[0062] In the present application, the granular ion sieve may be formed by water quenching. Preferably, the temperature of the water quenching is 10-80°C. In some embodiments, the temperature of the water quenching is 10°C, 15°C, 20°C, 22°C, 25°C, 30°C, 35°C, 45°C, 50°C, 60°C, 65°C, 70°C, 75°C, 80°C, etc., as well as ranges and subranges defined by any of the above values. In embodiments, any of the above ranges can be combined with any other range. The size of the ion sieve granules can be controlled by controlling the temperature, thereby making the particle size of the ion sieve granules meet 1-10 mm.
[0063] In some alternative embodiments, a sheet-shaped or porous ion sieve may be prepared according to the needs of use. Exemplarily, a sheet-shaped ion sieve may be formed by rolling or drawing with an external force. Preferably, the sheet-shaped ion sieve is an irregular sheet, with the shortest side of the sheet-shaped ion sieve being 0.3 cm or more, the longest side being less than 20 cm, and the thickness being 0.3 to 1.0 mm. For example, a porous ion sieve may be formed by introducing a foaming agent. Preferably, the pore size is 1 to 10 mm, and preferably, the shortest side of the porous ion sieve mass is 0.5 cm or more, and the longest side is less than 10 cm.
[0064] The ion sieve of the present invention can be used to remove impurities from a salt bath containing impurity ions, or can be directly introduced into a chemical strengthening process, and can adsorb / absorb lithium ions in a salt bath during the chemical strengthening process, making it widely usable.
[0065] In a third aspect, the present application provides a method for removing impurities from a salt bath for chemically strengthening glass. The method includes a step of introducing the ion sieve according to the first aspect into a salt bath for removing impurities to perform an adsorption reaction of impurity ions. The temperature of the salt bath for removing impurities is 350 to 550°C, and this temperature range is more advantageous in that the adsorption / absorption performance of the ion sieve for lithium ions can be fully exhibited. The impurity ions adsorbed / absorbed by the ion sieve are mainly lithium ions.
[0066] The term "impurity ions" here refers to ions that are not intentionally introduced into the salt bath when preparing the initial salt bath, such as lithium ions. The term "adsorption reaction" here refers to the adsorption of alkali metal ions with a large ionic radius in the ion sieve, such as K + OrNa + , impurity alkali metal ions with small ionic radii in the salt bath, e.g. Li + , and thereby impurity alkali metal ions in the salt bath are adsorbed onto the ion sieve, thereby realizing the removal of impurities from the salt bath.
[0067] In the present invention, "impurity removal from salt bath" may be online impurity removal, or impurity removal from salt bath after glass strengthening or salt bath containing excess impurity ions. Online impurity removal refers to directly introducing an ion sieve into an initial salt bath without impurity ions, for example, an ion sieve is placed in a carrier (such as a metal net) and placed in a salt bath, and the impurity removal process of the ion sieve (the process of adsorbing impurity ions in the salt bath) is carried out simultaneously with the glass strengthening process. Impurity removal from a salt bath after glass strengthening or a salt bath containing excess impurity ions refers to introducing an ion sieve into a salt bath containing impurity ions during or after the strengthening process is stopped, to perform an adsorption process of impurity ions.
[0068] In some alternative embodiments, the amount of the ion sieve used is 0.5 to 5.0% by weight of the salt bath for impurity removal. In the present application, a relatively small amount of the ion sieve can be used to effectively remove impurities from the salt bath, and the ion sieve according to the present application has excellent high temperature resistance and high temperature stability.
[0069] The salt bath for removing impurities according to the present application may be a potassium salt bath, a sodium salt bath, or a mixed salt bath of sodium and potassium (i.e., a mixed salt bath containing lithium (impurity ion), sodium, and potassium) containing a large amount of impurity lithium ions, and the above salt bath is preferably a nitrate bath.
[0070] The content of the lithium ion impurities in the salt bath for removing impurities according to the present application can be selected in a wide range, and the impurities can be removed by using the ion sieve according to the present application. For example, the content of the lithium ion impurities in the salt bath for removing impurities is 1 to 1000 ppm.
[0071] In some selectable embodiments, the reaction time is 0.1 to 48.0 hours. The ion sieve according to the present application has excellent impurity ion adsorption ability and can efficiently remove impurities from a salt bath containing impurity ions in a relatively short time. The ion sieve according to the present application has excellent high-temperature stability and can maintain a stable structure even in a high-temperature salt bath, and is unlikely to undergo significant crystal phase transition. Therefore, the ion sieve can continuously and stably adsorb impurity ions for 24 hours in a salt bath at 480°C, better realize online impurity removal, and do not need to frequently replace the salt bath or ion sieve material, which is more advantageous for improving mass production efficiency and reducing costs of chemically strengthened glass.
[0072] In a fourth aspect, the present application provides a method for preparing chemically strengthened glass. The method includes the steps of introducing a glass to be strengthened and an ion sieve according to the first aspect into a salt bath for chemically strengthening glass that is free of impurity ions, and chemically strengthening the glass to be strengthened to prepare chemically strengthened glass. The method is a method for realizing online impurity removal of the ion sieve, and realizing that the impurity removal process of the ion sieve is performed simultaneously with the tempering process of the glass, so that there is no need to pause the tempering process and there is no need to frequently replace the salt bath, which can improve the production efficiency of chemically strengthened glass and reduce the production cost of chemically strengthened glass.
[0073] According to this preparation method, in the process of chemical strengthening, the ion sieve of the present application can continuously and stably adsorb the impurity ions from the ion exchange process in the salt bath, so that the content of impurity ions in the salt bath can always be stably controlled at a relatively low level, and the quality of the tempered glass can be guaranteed; and the ion sieve hardly undergoes significant crystal phase transition, has a stable structure, does not release a large amount of impurity substances that pollute the salt bath, and can prevent the occurrence of defects such as significant granularity on the surface of the finished glass product after strengthening.
[0074] The salt bath free of impurity ions means a completely new salt bath containing almost no impurity ions, that is, an initial salt bath that has not been used for chemical strengthening of glass.
[0075] The present application will now be described in more detail with reference to specific examples. EXAMPLES
[0076] Example 1 Ion sieve is [ka] The values and oxide compositions are shown in Table 1 below. [ka] However, in the ion-sieving Raman spectrum, -1 Q after Gaussian deconvolution fitting to the bands in the range 3 is the corresponding area of Q 3 However, in silicon-oxygen tetrahedra with only one non-bridging oxygen, - Stretching vibration peak, [ka] However, in the ion-sieving Raman spectrum, -1 Q after Gaussian deconvolution fitting to the bands in the range 2 is the corresponding area of Q 2 However, in silicon-oxygen tetrahedra with only two non-bridging oxygens, Si-O - The initial XRD pattern of the ion sieve, i.e., the initial ion sieve that has not been used for salt bath impurity removal, is shown in Figure 1a.
[0077] As a preparation method, the raw material components of the ion sieve were weighed and mixed uniformly according to the formula shown in Table 1, and then melted at a temperature of 1500°C for more than 1 hour to form a liquid, and then quenched in water to form a granular ion sieve with a particle size of 2 to 5 mm. The water quenching temperature was 25°C.
[0078] (Examples 2 to 4) Each was carried out with reference to Example 1, but differed from Example 1 only in that the formulation instructions for the ion sieve were different. [ka] The content of each oxide and the relationship between the content of each oxide are specifically controlled, and the details are shown in Table 1. The initial XRD pattern of the ion sieve, i.e., the XRD pattern of the initial ion sieve that has not been used for salt bath impurity removal, is shown in Figure 1a.
[0079] (Comparative Examples 1 to 4) Each was carried out with reference to Example 1, but differed from Example 1 only in that the formulation instructions for the ion sieve were different. [ka] Specifically, this is achieved by controlling the content of each oxide and the relationship between the contents of each oxide, and the details are shown in Table 1. The initial XRD pattern of the ion sieve, i.e., the XRD pattern of the initial ion sieve that has not been used for salt bath impurity removal, is shown in Figure 1b.
[0080] (Application example 1) The ion sieves obtained in each of the above examples and comparative examples were placed in a test salt bath containing 105±10 ppm lithium ions at 480° C. to carry out a lithium ion adsorption reaction. The amount of the ion sieve used was 1% by weight of the test salt bath. In the above test salt bath, the change in lithium ion concentration y over time x is shown in Table 2 and Figures 3a and 3b below, and the fitting results of the change curves in Examples 1 to 4 are shown in Figures 4, 5, 6 and 7. After the ion sieve adsorbed lithium ions in the test salt bath for 24 hours, the crystal content in the ion sieve was shown in Table 1 below. The crystal content was expressed as the percentage of the crystal peak area in the XRD pattern of the ion sieve after 24 hours of salt bath impurity removal. The XRD patterns of the ion sieves after 24 h of salt bath impurity removal are shown in Figures 2a and 2b, respectively.
[0081] [Table 1]
[0082] [Table 2]
[0083] As can be seen from Tables 1 and 2, the ion sieves according to the examples of the present invention are all superior to the comparative examples. [ka] By using a formula in which the formula is greater than 1, lithium ions can be continuously and stably adsorbed in a test salt bath at 480°C for 24 hours, and the crystal content in the ion sieve after adsorbing lithium ions for 24 hours is less than 10% by weight in each case. As can be seen, the ion sieve according to the embodiment of the present invention has a stable absorption ability for lithium ions in a high-temperature salt bath, little or no crystal phase transition occurs in the high-temperature salt bath, and can maintain a stable structure for a long time, and will not contaminate the high-temperature salt bath or shorten the life of the salt bath due to the long-term introduction of the ion sieve.
[0084] As can be seen from FIGS. 1a, 1b, 2a and 2b, after the ion sieve according to the embodiment of the invention of the present application continuously carried out impurity removal for 24 hours in a salt bath for testing at 480°C, almost no crystal phase transition occurred and a stable structure was maintained. In contrast, for the ion sieve according to the comparative example, after continuously carrying out impurity removal for 24 hours in a salt bath for testing at 480°C, a significant crystal phase transition occurred and a large number of crystals not contained in the initial ion sieve were generated. As can be seen from this, the ion sieve according to the invention of the present application having a specific composition and a specific structure has excellent high-temperature stability and can continuously remove impurity ions in a high-temperature salt bath for a long time.
[0085] As can be seen from FIGS. 3a, 3b and 4 to 7, after the ion sieve according to the embodiment was placed in a salt bath for testing at 480°C to remove lithium ion impurities, the change in the lithium ion concentration y in the salt bath with the passage of time x satisfied the function of y = A1×exp(-x / b1)+A2×exp(-x / b2)+C0, where 100 > A1 > 30, 0 < A2 < 31, 0 < b1 < 5, 0 < b2 < 25, and 0 < C0 < 50, and exp is an exponential function. As can be seen from this, the ion sieve having a specific composition and a specific structure according to the embodiment of the invention of the present application can adsorb lithium ions continuously and stably for a long time in a high-temperature salt bath.
[0086] In contrast, the ion sieves according to the comparative examples did not satisfy the above function regarding the time change of the lithium ion concentration in the salt bath at 480° C. For example, the fitting function corresponding to the comparative example 2 was y=29×exp(-x / 1.52)-10.92×exp(x / 22.00)+79.89. The ion sieves according to the comparative examples 1 and 4 released lithium ions from the ion sieve to the salt bath before 10 hours of impurity removal had elapsed, which increased the lithium ion concentration in the salt bath. In other words, the comparative examples did not satisfy the characteristics of the ion sieve having the specific composition and specific structure according to the present invention, and could not continuously and stably adsorb lithium ions for a long time in the high-temperature salt bath, and released lithium ions into the salt bath due to the change in structure in the latter half.
[0087] (Application example 2) Taking Example 1, Comparative Example 1 and Comparative Example 2 as examples, the ion sieve and the lithium aluminosilicate glass to be tempered were simultaneously put into a completely new sodium nitrate salt bath at 460°C and tempered in a continuous batch manner. The tempering time for each batch was 8 hours. After one batch of glass tempering was completed, the tempered glass and the ion sieve were both removed from the salt bath, and the next batch of glass to be tempered and a new ion sieve were added. The amount of the ion sieve used in each tempering was 1% of the weight of the salt bath together with the glass to be tempered. When the eighth batch of tempering was reached, the drawings showing the finished glass products obtained by Example 1 and Comparative Examples 1-2 are shown in Figures 8, 9 and 10.
[0088] As shown in Fig. 8, when salt-bath impurity removal was performed using the ion sieve according to Example 1 of the present invention, the tempered glass had a smooth surface and was free of defects. In contrast, when salt-bath impurity removal was performed using the ion sieves according to Comparative Examples 1 and 2, noticeable granular defects appeared on the surface of the tempered glass, as shown in the dotted circle in Figs. 9 and 10.
[0089] Although the above describes the optional embodiments of the present invention in detail, the present invention is not limited thereto. Within the scope of the technical idea of the present invention, various simple modifications may be made to the technical idea of the present invention, such as combining each technical feature in any other suitable manner. These simple modifications and combinations should also be considered as the contents disclosed in this application, and all belong to the protection scope of the present invention. [Industrial Applicability]
[0090] The present application belongs to the technical field of ion sieves, in particular to the technical field of removing impurities from salt baths for chemically strengthening glass, and specifically to an ion sieve having high temperature resistance and high temperature stability, its preparation method and use. In terms of the mole percentage of each oxide in the ion sieve, the composition of the ion sieve includes 46-60 mol% of SiO2, 3-16 mol% of Al2O3, 0-3 mol% of Y2O3 and 33-45 mol% of R2O. R2O is an alkali metal oxide. The ion sieve is [ka] is greater than or equal to 1. The ion sieve of the present invention has excellent high temperature resistance and high temperature stability, and even when placed in a high temperature salt bath for a relatively long time, it hardly undergoes significant crystal phase transition, has a stable structure, does not release a large amount of impurity substances that contaminate the salt bath, and does not cause significant defects on the surface of the finished glass product after tempering. The ion sieve of the present invention can continuously and stably adsorb impurity ions for 24 hours in a salt bath at 480°C.
[0091] It should be noted that the ion sieve with high temperature resistance and high temperature stability, its preparation method and use according to the present application are feasible and can be applied to various industrial applications. For example, the ion sieve with high temperature resistance and high temperature stability, its preparation method and use according to the present application can be applied to the technical field of ion sieving.
Claims
1. An ion sieve having high temperature resistance and stability, The composition of the ion sieve is SiO 2 46 to 60 mol %, Al 2 O 3 3 to 16 mol %, Y 2 O 3 0 to 3 mol % and R 2 O 33 to 45 mol %; R 2 O is an alkali metal oxide; The ion sieve comprises: 【Chemistry 1】 is 1 or more, 【Chemistry 2】 However, in the ion sieving Raman spectrum, -1 Q after Gaussian deconvolution fitting to the bands in the range 3 is the corresponding area of Q 3 but Si-O in a silicon-oxygen tetrahedron having only one non-bridging oxygen - Stretching vibration peak, 【Chemistry 3】 However, in the ion sieving Raman spectrum, -1 Q after Gaussian deconvolution fitting to the bands in the range 2 is the corresponding area of Q 2 but Si-O in a silicon-oxygen tetrahedron having only two non-bridging oxygens - Stretching vibration peak An ion sieve having high temperature resistance and high temperature stability, characterized in that
2. After placing the ion sieve in a salt bath at 480° C. for 24 hours, the ion sieve has a crystal content of less than 10% by weight.
2. The ion sieve of claim 1 . 【Request 3】 【Chemical 4】 teeth 【Chemistry 5】 Fulfill 3. The ion sieve according to claim 1 or 2.
4. The composition of the ion sieve is 52.0 ≧ 0.85 × SiO 2 + 0.15 x Al 2 O 3 +1.65 x Y 2 O 3 Satisfy ≧45.3 The ion sieve according to any one of claims 1 to 3.
5. The composition of the ion sieve is such that the mole percentage of each oxide in the ion sieve is 20.0 ≧ 0.50 × R 2 O≧16.0 and R 2 O is Na 2 O and / or K 2 O, and preferably R 2 O is Na 2 It is O.
5. The ion sieve of claim 4.
6. In the ion sieve, SiO 2 is 49 to 60 mole %; and / or A 2 O 3 is from 3 to 15 mole %; and / or Y 2 O 3 is 1 to 3 mole %; and / or R 2 The mole percentage of O is 33 to 40 mole %. The ion sieve according to any one of claims 1 to 5.
7. The composition of the ion sieve is ZnO 0-3 mol%, CaO 0-3 mol%, MgO 0-3 mol%, P 2 O 5 0 to 3 mol %, and B 2 O 3 0 to 3 mol % of ZnO+CaO+MgO+P 2 O 5 +B 2 O 3 The sum of the mole percentages of The ion sieve according to any one of claims 1 to 6.
8. In the ion sieve, P 2 O 5 And / or B 2 O 3 Contains almost no 8. The ion sieve of claim 7 .
9. When the ion sieve having a mass percentage of 1 wt. % based on the mass of the salt bath is placed in a salt bath at 480° C. containing 105±10 ppm of impurity lithium ions, The change curve of the lithium ion concentration y in the salt bath over time x is y = A 1 ×exp(-x / b 1 ) + A 2 ×exp(-x / b 2 ) + C 0 where exp is an exponential function, and A 1 100>A 1 >30, A 2 is 0 < A 2 <31, b 1 is 0<b 1 <5, b 2 is 0<b 2 <25, C 0 is 0 < C 0 < 50, where x is in hours The ion sieve according to any one of claims 1 to 8.
10. The ion sieve is granular, sheet or porous, preferably granular, and preferably the particle size of the granular ion sieve is 1 to 10 mm. The ion sieve according to any one of claims 1 to 9.
11. A method for preparing the ion sieve according to any one of claims 1 to 10, comprising the steps of: The preparation method includes the steps of weighing and uniformly mixing each raw material according to the recipe, melting it at a temperature of 1300-1650°C to obtain a liquid material, and preparing it into a granular, sheet or porous form. A method for preparing an ion sieve comprising the steps of:
12. The granular ion sieve is formed by water quenching, and the water quenching temperature is 10-80°C. A method for preparing an ion sieve according to claim 11 .
13. Forming sheet-like ion sieves by rolling or drawing with external force A method for preparing an ion sieve according to claim 11 .
14. Forming a porous ion sieve by introducing a foaming agent A method for preparing an ion sieve according to claim 11 .
15. The method includes a step of introducing the ion sieve according to any one of claims 1 to 10 into a salt bath for removing impurities at 350 to 550°C to perform an adsorption reaction of impurity ions. A method for removing impurities from a salt bath for chemically strengthening glass, comprising:
16. The amount of the ion sieve used is 0.5 to 5.0% by weight of the salt bath for removing impurities, and / or the time of the adsorption reaction is 0.1 to 48.0 hours. The method for removing impurities according to claim 15.
17. The content of impurity ions in the salt bath for removing impurities is 1 to 1000 ppm. The method for removing impurities according to claim 16.
18. The method includes a step of introducing a glass to be tempered and the ion sieve according to any one of claims 1 to 10 into a salt bath for chemically strengthening glass that is free of impurity ions, and chemically strengthening the glass to be tempered. A method for preparing chemically strengthened glass, comprising the steps of:
Citation Information
Patent Citations
Boron-free phosphorus-free high-stability ion sieve and application thereof
CN112645610A
Methods of regenerating poisoned molten salt baths with glass and associated glass compositions
US20210403377A1
Life extension method for molten salt composition, manufacturing method for chemically strengthened glass, glass auxiliary agent, and raw material for glass
WO2020218253A1